Telaah Epistemologi Positivisme dan Fenomenologi (Sebuah Perbandingan) - -, M. Sanusi (ASKETIK, 2018)
Epistemology is begun based on the need of philosophy used to recite social-cultural events. Nowadays, development of epistemology is fast enough as a proof of a thinking way which is growing in academic and reasearch, especially in social-cultural science. The growing epistemology are positivism, materialism, structuralism, hermeneutics and phenomenology. Epistemology does not appear explicitly in reasearch yet it is always there. Scientists and researchers should be aware what epistemology is to use. It gives the benefit in the strenghth of the research. This article delivers about growing epistemology in social sciences. The two kinds of epistemology discussed in this article used comparison approach; that is comparing both to find out the similarities and the differences. Positivism is epistemology used in many social-cultural researchs while phenomenology responds positivism and shows critic on it.